RELEVANSI PEMIKIRAN IKHWAN AL-SHAFA BAGI PENGEMBANGAN DUNIA PENDIDIKAN - Furqon Syarif Hidayatullah (Ta'dib: Jurnal Pendidikan Islam, 2013)
Ikhwan Al-Shafa is a wellknown person in education. His theory of education is very relevant to recent theory of education. He also proposed the aim of education, law of learning curricullum, method of teaching-learning and the profile of education and student.